Pemetaan Pola Perjalanan Wisata di Desa Ngargoretno, Salaman, Magelang Jawa Tengah - Adi Hendraningrum; Indriyani Handyastuti; Ina Veronika Ginting; Iqlima Ramadhani; Singgih Tri Wibowo (Politeknik Pariwisata NHI Bandung, 2022)
The Ngargoretno Tourism Village has experience an increase in tourism activities in recent times along with the increase in attractions and the number of visitors, especially after the pandemic. To be able to provide an experience that is accordance with the tourism concept of the Ngargoretno Tourism Village which launched educational tourism, it is considered necessary to provide a choice of various forms of travel patterns that are formed according to the character of the tourist village destination of Ngargoretno and the character of visiting tourist. The theory used in making the travel pattern of this research is Lew and McKercher (2016). The method used in this study is a descriptive method with a qualitative approach. The analytical technique used in making the travel pattern uses four approaches, namely, the process of collecting data, reducing data, presenting data and drawing conclusions. The four analytical techniques were carried out to analyze the data obtained from the results of this research and get conclusions about the research carried out. The data collection tool used is an interview guide. This research was conducted as an effort so that the research results can be used as a basis for reference for the tourism stakeholders of Ngargoretno Village and the government of Magelang Regency to be able to design tourism activity development programs, and it is hoped that this research will become a recommendation for relevant stakeholders who will develop and promote Ngargoretno as a Tourism Village that acts as a buffer for orobudur as a Super Priority Tourist Destiantion Area.